2012
DOI: 10.1186/1471-2458-12-259
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of factors associated with the health and well-being of HIV-infected or HIV-affected older people in rural South Africa

Abstract: Background Despite the severe impact of HIV in sub-Saharan Africa, the health of older people aged 50+ is often overlooked owing to the dearth of data on the direct and indirect effects of HIV on older people’s health status and well-being. The aim of this study was to examine correlates of health and well-being of HIV-infected older people relative to HIV-affected people in rural South Africa, defined as participants with an HIV-infected or death of an adult child due to HIV-related cause. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 52 publications
7
69
2
1
Order By: Relevance
“…In this cohort 51.9% of the participants scored 2 or more on the WHODAS 2.0 using the adjusted measure [14,28,29]. This is higher than in the sister study in KZN [6] and suggest a high prevalene of functional limitations that if not addressed may be a risk of disability.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In this cohort 51.9% of the participants scored 2 or more on the WHODAS 2.0 using the adjusted measure [14,28,29]. This is higher than in the sister study in KZN [6] and suggest a high prevalene of functional limitations that if not addressed may be a risk of disability.…”
Section: Discussioncontrasting
confidence: 54%
“…This is higher than in the sister study in KZN [6] and suggest a high prevalene of functional limitations that if not addressed may be a risk of disability. In many studies, disability is described differently and often interchangeably between functional and activity limitation, disability and functioning [5], [28][29][30]. Current measures of disability such as the WHODAS on muscle function as well as aptotic effects on muscle cells [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study in Malawi indicated that older women were more likely to be disabled than older men [12]. Even among HIV infected populations in South Africa, older women were still at a higher risk of disabilities compared to older men [13]. Studies in middle income countries have also reported increased disability among older women [14] [15].…”
Section: Older Persons and Disabilitymentioning
confidence: 99%
“…Prevalence of activity limitations and participation restrictions was 80% and 93%, respectively. In Southern Africa, the ICF has been used to study HIV in four studies [7,16,17,20], each of which describes a diverse experience of disability among people living with HIV.…”
Section: Introductionmentioning
confidence: 99%